2016
DOI: 10.1016/j.elecom.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

What happens to inorganic nitrogen species during conductive diamond electrochemical oxidation of real wastewater?

Abstract: This work describes the oxidation of caffeine, metoprolol, SMX and progesterone in real wastewater in terms of inorganic nitrogen speciation and help to clarify the mechanisms that affect inorganic nitrogen species as final products. In synthetic solutions containing ammonium or nitrates ions, it has been confirmed that reduction of nitrates is a very favored process while oxidation of ammonium is negligible. Role of chloride is demonstrated to be important in the formation of chloramines, as well. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Similarly, the stoichiometric H 2 O 2 dose led to 35% TN recovery in the form of NO 3 − and NO 2 − . The N mass balance also was incomplete, probably because of the release of N‐containing byproducts such as chloramines or gaseous nitrogen oxides (N x O y ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the stoichiometric H 2 O 2 dose led to 35% TN recovery in the form of NO 3 − and NO 2 − . The N mass balance also was incomplete, probably because of the release of N‐containing byproducts such as chloramines or gaseous nitrogen oxides (N x O y ) …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the stoichiometric H 2 O 2 dose led to 35% TN recovery in the form of NO 3 − and NO 2 − . The N mass balance also was incomplete, wileyonlinelibrary.com/jctb probably because of the release of N-containing byproducts such as chloramines 48 or gaseous nitrogen oxides (N x O y ). 47,49 Ecotoxicity and biodegradability Fenton-like oxidation was used here to increase the biodegradability of the effluent before its biological treatment.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for effluents of Fenton oxidation with lower H2O2 doses, the concentration of nitrite and nitrate became more similar (4 mg L -1 for NO2and 4.5 mg L -1 for NO3 -), indicating an increase in the oxidation rate was related with the high conversion of nitrite in nitrate. For all the H2O2 doses, the nitrogen mass balance was incomplete, due to the possible formation of nitrogen-containing by-products as chloramines (Vidales et al 2016) and NOx species in gas phase (Garcia-Segura et al 2017).…”
Section: Figmentioning
confidence: 99%
“…Finally, the chlorine balance was almost completely closed. Probably, the unidentified fraction could corresponds to the formation of chloramines (Vidales et al 2016) or other chlorine species. Comparing these results with those described for Fenton oxidation of ionic liquids separately, it can be concluded that the presence of both compounds lead to similar results in terms of IL removal, mineralization of the starting compounds and COD conversion and no synergistic effect, interference or competition between HmimCl and BmpyrCl was observed.…”
Section: Figmentioning
confidence: 99%
“…where Δ[TOC] t is the measured TOC removal (mg L −1 ) after a certain treatment time, t (h), n the number of exchanged electrons (see Eq. 2and assuming that only NO 3 − ions are produced [37]) considering that the applied electric charge was consumed solely by the mineralization process, F the Faraday constant (96485C mol −1 ), V the solution volume (L), 4.32 × 10 7 is a compounded conversion factor…”
Section: Analysesmentioning
confidence: 99%